Effect of Cr content on the passivation behavior of Cr alloy steel in a CO2 aqueous environment containing silty sand. (15th May 2020) - Zhao, Yonggang; Liu, Wei; Fan, Yueming; Fan, Endian; Dong, Baojun; Zhang, Tianyi; Li, Xiaogang
Highlights: High Fe3 C content accelerated the formation of a passive film on the Cr steel surface in silty sand containing solution. Increasing Cr content in steel enhanced the contents of Cr2 O3 and Cr(OH)3 in the passive film. Silty sand increased carrier densities of the passive films and reduced the protective effects of the films. Corrosion mechanism of the Cr steel with silty sand based on the combined effect of Fe3 C and Cr contents was illustrated. Abstract: The effect of Cr content in steel on its passivation behavior in a CO2 aqueous environment containing silty sand was investigated. The results indicated that the stability of passive film was improved with increasing Cr content. High Fe3 C content accelerated the rapid formation of a passive film as well as precipitates and dislocations. Increasing Cr content enhanced the contents of Cr2 O3 and Cr(OH)3 in the passive film. Silty sand increased carrier densities of passive films, thereby reducing their protective effects. The role of the contents of Fe3 C and Cr on corrosion mechanism of Cr steel with silty sand was emphasized.